Predicting the structural response of a compartment fire using full-field heat transfer measurements. (July 2017) - Hodges, Jonathan; Rippe, Christian; Case, Scott W.; Lattimer, Brian Y.
Abstract: Inverse heat transfer analysis (IHT) was used to measure the full-field heat fluxes on a small scale (0.9 m×0.9 m×0.9 m) stainless steel SS304 compartment exposed to a 100 kW diffusion flame. The measured heat fluxes were then used in a thermo-mechanical finite element model in Abaqus to predict the response of an aluminum 6061-T6 compartment to the same exposure. Coupled measurements of deflection and temperature using Thermographic Digital Image Correlation (TDIC) were obtained of an aluminum compartment tested until collapse. Two convective heat transfer coefficients, h =35 W/m 2 -K and h =10 W/m 2 -K were examined for the thermal model using the experimentally measured heat fluxes. Predictions of the thermal and structural response of the same compartment were generated by coupling Fire Dynamics Simulator (FDS) and Abaqus using the two values for h, h =35 W/m 2 -K and h from convection correlations. Predictions of deflection and temperature using heat fluxes from IHT and FDS with h =35 W/m 2 -K agreed with experimental measurements along the back wall. The temperature predictions from the IHT-Abaqus model were independent of h, whereas the temperature predictions from the FDS-Abaqus model were dependent on h .